Spectra and Charge Transport of Polar Molecular Photoactive Layers Used for Solar Cells - Yuanzuo Li; Dawei Qi; Chaofan Sun; Meiyu Zhao (Journal of Chemistry)
The ground state structures, HOMO and LUMO energy levels, band gaps ΔH-L, ionization potentials (IP), and electron affinities (EA) of three types of copolymer P1 and its derivatives P2, P3, and PBDT-BTA were investigated by using density functional theory (DFT) with B3LYP and 6-31G (d) basis set. On the base of optimized structures of ground states, their absorption spectra were obtained by using TD-DFT//Cam-B3LYP/6-31 G (d). Research shows that with the increasing conjugated units, HOMO energy levels increased, LUMO energy levels decreased, and band gaps decreased gradually. Moreover, their ionization potentials decreased and electron affinities increased along with the increase of conjugated chains, and absorption spectra red-shifted. In addition, the side chain has a significant effect on the properties of ground and excited states. In order to investigate the influence of conjugated units and side chain on the charge transport, their hole and electron reorganization energies were calculated, and the results indicated that Pb have a good hole transport capability. Considering the practical application, the HOMO and LUMO energy levels, band gaps, and absorption spectra under external electric field were studied, and the results proved that the external electric field has an effect on the optical and electronic properties.